Measuring the Future of Indonesia's Creative Economy: A Statistical and SWOT Analysis Toward Golden Indonesia 2045 - Pangestika, Ratna Rosita; Nurul Hidayah; Niken Purnamasari (Sinergi International Journal of Economics, 2026)
The creative economy has become a strategic pillar of Indonesia’s national development, contributing approximately IDR 1,389 Quadrillion Rupiah to GDP in 2024 at current prices and employing more than 24 million workers, based on data from Statistics Indonesia and the Ministry of Tourism and Creative Economy. Using the national classification of creative economy subsectors, this study analyzes development trends, projects future growth toward the Golden Indonesia 2045 agenda, and evaluates strategic positioning through a SWOT framework. This research adopts a descriptive quantitative secondary-data design using time-series data from 2010-2024 derived from Statistics Indonesia, the Ministry of Tourism and Creative Economy, and national planning documents. Analytical techniques include descriptive statistics, trend and projection modeling, and an integrated SWOT analysis linking sectoral indicators with long-term policy targets. The study’s novelty lies in combining projection modeling with subsectoral analysis and aligning strategic evaluation with national development goals. The findings indicate sustained growth with the potential for the creative economy to contribute around 10% of national GDP by 2045. However, challenges remain in financing access, digital infrastructure, and intellectual property governance, highlighting the need for cross-sectoral collaborative policy strategies.